THE FEMALE PRESENCE IN THE HIPHOPMOVEMENT: SOCIALINCLUSION FROM THE BREAKDANCE (Fiep Bulletin - online, 2013)
The study interprets the reasons which lead young women from Pedra de Guaratiba, west outskirts of Rio de Janeiro, to get involved and stay with the dance movements of hip hop, and examines the process of social inclusion of young people sponsored by participation in youth movement. The group is unique because 70% are women who dance the genuine break. The research proposal follows the Analysis of Speech of Collective Subject, which operates a "trialogue" between the discourses of the individual subject, collective subject and ethnography. The results confirm the reasons for the predominance of women, who dance for pleasure and for the overrun of force by the technique. The motive for the break, welcomed and encouraged by the leaders, shows a gender dispute, in which the dancers are involved in the construction of a reflexive project of self and belonging to a group. The proposal favors the female self in the implementation of the break, shows the pride the dancer's movement causes in the leaders and contributes to the recovery collectivization.
Keywords: women; hip hop; social inclusion